Anti-perovskite positive electrode material, preparation method thereof and lithium ion battery
During the preparation of the positive electrode material of anti-perovskite lithium-ion battery, wet gel is generated by hydrolysis and polymerization, and Li2MxNySO is obtained through heat treatment, which solves the problem of poor circulation and rate performance of existing materials, and achieves more uniform particle distribution and better battery performance.
Patent Information
- Application Number
- CN202411883255.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing anti-perovskite lithium-ion battery positive electrode materials have problems such as low voltage platform, inability to fully release capacity, and poor circulation performance and rate performance.
By mixing the metal salt containing metal M with ethyl thiol and water for hydrolysis, the pH of the product solution is adjusted to 2-4, and adding metal salt containing metal N, lithium ethanol, polymeric monomer, crosslinking agent and initiator for polymerization to form a wet gel, and the anti-perovskite-type positive electrode material Li2MxNySO is obtained through heat treatment.
This method makes the particle size inside the cathode material smaller and the particle distribution more uniformly, thereby improving the circulation and rate performance of lithium-ion batteries.
Smart Images

Figure CN119683692A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to an anti-perovskite positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] In the short history of development of lithium-ion batteries over the past few decades, they have played an important role in electronic products, transportation, aerospace, etc. Generally speaking, lithium-ion batteries are composed of materials such as positive electrodes, electrolytes, separators, negative electrodes, and current collectors. Among these components, the positive electrode material is the main factor limiting the capacity, and its cost is also the highest among all battery accessories. The widely studied positive electrode materials include polyanion olivine-structured LiFePO4, layered LiCoO2, high-nickel ternary material NCM811, spinel-structured LiMn2O4, etc.
[0003] Li represented by polyanionic structure 1-x FePO4, due to its poor ionic and electronic conductivity, usually requires small particles to be coated with carbon, which has problems such as low tap density, low energy density, and poor low temperature performance. 1-x CoO2, because Co itself is easily soluble, expensive and harmful to the environment, has problems such as capacity attenuation, poor safety, environmental pollution, and high cost. 1+x Mn2O4, due to the disproportionate dissolution of Mn, has problems such as short life, poor high-temperature performance, gas generation, and blistering.
[0004] The recently proposed new lithium-ion battery positive electrode material with anti-perovskite structure has a high theoretical specific capacity, but it also has various problems: including low voltage platform, inability to fully release capacity, poor cycle performance and rate performance, etc. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing a method for preparing an anti-perovskite positive electrode material so that the particle size of the internal particles of the positive electrode material is smaller and the internal particle distribution is more uniform, thereby improving the cycle performance and rate performance of lithium-ion batteries.
[0006] In a first aspect, the present invention provides a method for preparing an antiperovskite cathode material, comprising: mixing a metal salt containing a metal M with ethanethiol and water to perform a hydrolysis reaction to obtain a product solution; adjusting the pH of the product solution to 2-4, adding a metal salt containing a metal N, lithium ethoxide, a polymerization monomer, a crosslinking agent and an initiator to the product solution to perform a polymerization reaction to generate a wet gel; drying the wet gel and then performing a heat treatment to obtain an antiperovskite cathode material Li2M x Ny SO; wherein 0<x<1, 0<y<1; M and N are different and are metal elements or metalloid elements other than lithium; the metal salt comprises carboxylate and / or alkoxide; the polymerization monomer comprises vinyl monomer or propenyl monomer.
[0007] In the preparation method, under the initiation of an initiator, a cross-linking agent is used to cause a polymerization reaction of free radicals of a polymerizable monomer to form a three-dimensional network gel structure; at the same time, a metal salt containing metal N, lithium ethanol and a hydrolysis product react to form antiperovskite inorganic particles. Due to the existence of the three-dimensional network structure, the inorganic particles can be prevented from agglomerating, which plays a role in refining the grains and can also make the grains uniformly dispersed in the wet gel; and then heat treatment is performed to fully volatilize the gelled organic matter, thereby obtaining nano-sized Li2M x N y SO crystals. Through such a preparation method, the internal particle size of the antiperovskite positive electrode material can be made smaller and the internal particle distribution more uniform, thereby improving the cycle performance and rate performance of the lithium-ion battery.
[0008] In some embodiments of the present application, M and N each independently include any one of Na, K, Mg, Ca, Sr, Ba, Zn, Sc, Y, Al, Ga, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Si, Sn and Sb.
[0009] In some embodiments of the present application, the metal salt includes at least one of manganese acetate, sodium acetate, iron ethoxide and cobalt ethoxide.
[0010] In some embodiments of the present application, the acrylic monomer includes acrylamide.
[0011] In some embodiments of the present application, the vinyl monomer includes any one of ethylene, propylene and acrylic acid.
[0012] After the polymerization reaction of the polymerization monomer, a cross-linked structure is formed, which can wrap and disperse the particles of the metal salt containing metal M and the metal salt containing metal N. This helps to increase the uniformity of the material, improve the dispersion of the particles, and refine the grains, thereby improving the performance of the positive electrode material of the lithium-ion battery. Vinyl monomers or propylene monomers are selected as polymerization monomers because they can provide the required network structure in this preparation method, which helps to improve the performance of the material, including particle dispersion and grain refinement, thereby improving the performance of the positive electrode material of the lithium-ion battery.
[0013] In some embodiments of the present application, the crosslinking agent includes any one of N,N-methylenebisacrylamide and divinyldisiloxane. N,N-methylenebisacrylamide and divinyldisiloxane have high crosslinking ability and can form a three-dimensional network gel structure in the polymerization reaction, which is used to support the anti-perovskite crystals dispersed in the wet gel. Due to the presence of the three-dimensional network structure, the agglomeration of the grains can be prevented, and the grain distribution can be made more uniform, thereby improving the electrochemical performance of the positive electrode material of the lithium-ion battery. At the same time, these two compounds also have good chemical stability, are not easy to decompose, and are conducive to improving the cycle life of the material.
[0014] In some embodiments of the present application, the initiator includes ammonium persulfate. Ammonium persulfate is a free radical initiator that can initiate a free radical polymerization reaction of a polymerizable monomer and promote the formation of a polymer. In this preparation method, it helps to form a wet gel and catalyzes the polymerization reaction, ultimately generating a lithium-ion battery positive electrode material with a good structure. Ammonium persulfate is easy to use and has high efficiency.
[0015] In some embodiments of the present application, the temperature of the hydrolysis reaction is 20-25° C., and the time of the hydrolysis reaction is 6-8 hours. Controlling the temperature and time of the hydrolysis reaction within the above range can make the hydrolysis reaction more complete and generate the important intermediates or precursors for the preparation of the desired antiperovskite cathode material.
[0016] In some embodiments of the present application, the polymerization temperature is 20-25°C, and the polymerization time is 10-14h. Controlling the polymerization temperature and time within the above range is conducive to better controlling the free radical polymerization of the polymerization monomer during the reaction. This can slow down the polymerization reaction rate and help the polymerization process to proceed fully, thereby forming a uniform network structure and making the internal particle distribution of the entire wet gel more uniform.
[0017] In some embodiments of the present application, the drying temperature is 105-120°C and the drying time is 8-10 hours. Within this temperature range, water can be effectively evaporated from the wet gel. This helps to reduce the water content in the material and improve the stability of the material.
[0018] In some embodiments of the present application, the heat treatment temperature is 300-500°C and the heat treatment time is 5-7h. Heat treatment at 300-500°C for 5-7h can fully volatilize the organic matter remaining in the wet gel, reduce the content of organic residues in the material, and thus improve the thermal stability of the material.
[0019] In some embodiments of the present application, the amount of polymerization monomer added is 20-30% of the total mass of the product solution. Adding 20-30% polymerization monomer is conducive to allowing enough monomers to participate in the polymerization reaction and form enough cross-linking structures, which can effectively prevent particle aggregation, thereby providing suitable support and dispersion effects.
[0020] In some embodiments of the present application, the amount of cross-linking agent added is 20-30% of the total mass of the product solution. Adding 20-30% of the cross-linking agent can effectively form a cross-linked structure and increase the stability and durability of the material.
[0021] In some embodiments of the present application, the amount of initiator added is 20-30% of the total mass of the product solution. Adding 20-30% of the initiator is conducive to the initiation reaction, so that the polymerized monomers form a polymer network structure, and the polymerization reaction is more complete.
[0022] In some embodiments of the present application, the particle size of the antiperovskite positive electrode material is 50-100 nm.
[0023] In a second aspect, an embodiment of the present application provides an anti-perovskite positive electrode material prepared by the above-mentioned preparation method.
[0024] In a third aspect, an embodiment of the present application provides a lithium-ion battery comprising the above-mentioned antiperovskite positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 The antiperovskite cathode material Li2Fe prepared in Example 1 of the present application 0.5 Mn 0.5 XRD pattern of SO;
[0027] Figure 2 The antiperovskite cathode material Li2Fe prepared in Example 1 of the present application 0.5 Mn 0.5 SEM image of SO;
[0028] Figure 3 The charge and discharge curve of a battery prepared with the positive electrode material provided in Example 1 of the present application;
[0029] Figure 4 This is a rate performance diagram of a battery prepared using the positive electrode material provided in Example 1 of the present application. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0031] The present application provides a method for preparing an antiperovskite positive electrode material, comprising:
[0032] (1) Mixing a metal salt containing metal M with ethanethiol and water, stirring at 20-25° C. for 2-3 hours using a magnetic stirrer, and performing a hydrolysis reaction to obtain a product solution. The purpose of the hydrolysis reaction is to generate important intermediates or precursors for the preparation of the desired antiperovskite cathode material, which include metal ions (M), sulfide ions (S 2- ), and other possible ions and ligands.
[0033] In the present application, the temperature of the hydrolysis reaction is 20-25°C, and the time of the hydrolysis reaction is 6-8h. This is equivalent to carrying out the hydrolysis reaction at room temperature, and controlling the time of the hydrolysis reaction to be 6-8h can make the hydrolysis reaction more complete.
[0034] The metal M includes any one of Na, K, Mg, Ca, Sr, Ba, Zn, Sc, Y, Al, Ga, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Si, Sn and Sb. The metal N includes any one of Na, K, Mg, Ca, Sr, Ba, Zn, Sc, Y, Al, Ga, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Si, Sn and Sb.
[0035] (2) Using nitric acid to adjust the pH of the product solution to 2-4, a metal salt containing metal N, lithium ethanol, a polymerization monomer, a cross-linking agent and an initiator are added to the product solution to generate a wet gel, and the free radicals of the polymerization monomer undergo a polymerization reaction to form a three-dimensional network structure support dispersed in the wet gel.
[0036] The pH of the product solution is adjusted to 2-4 because under this acidic condition, the hydrolysis reaction and polymerization process can be better controlled, so that the synthesis reaction can proceed smoothly. 2+ ) and sulfide ions (S 2-) is more likely to undergo hydrolysis reaction to generate the desired intermediate. Moreover, within the above pH range, the free radicals of the polymerization monomers can be better promoted to undergo polymerization reaction to form a three-dimensional network structure, which helps to prevent particle agglomeration and achieve uniform dispersion of fine grains.
[0037] In the present application, the metal salt includes carboxylates and / or alkoxides; moreover, the metal salt of metal M can be a carboxylate or an alkoxide; similarly, the metal salt of metal N and the metal salt of metal M can be a carboxylate or an alkoxide.
[0038] The metal salt includes, but is not limited to, at least one of manganese acetate, sodium acetate, iron ethoxide, and cobalt ethoxide.
[0039] The polymerizable monomers include vinyl monomers or propenyl monomers; propenyl monomers include but are not limited to acrylamide; vinyl monomers include but are not limited to any one of ethylene, propylene and acrylic acid. After the polymerizable monomers undergo polymerization, a cross-linked structure is formed, which can wrap and disperse the particles of the metal salt. This helps to increase the uniformity of the material, improve the dispersion of the particles, and refine the grains, thereby improving the performance of the positive electrode material for lithium-ion batteries. The reason for selecting vinyl monomers or propenyl monomers is that they have good polymerization properties and appropriate chemical properties in the polymerization reaction. These two monomers are generally easy to polymerize and can be polymerized under acidic conditions. In addition, their polymerization reactions can generally be carried out at relatively low temperatures, which is suitable for this application.
[0040] In the present application, the crosslinking agent includes but is not limited to any one of N,N-methylenebisacrylamide and divinyldisiloxane; the initiator includes but is not limited to ammonium persulfate. N,N-methylenebisacrylamide and divinyldisiloxane have high crosslinking ability and can form a three-dimensional network structure in the polymerization reaction, which is used to support the anti-perovskite crystals dispersed in the wet gel. This helps to prevent the agglomeration of the grains and make the grain distribution more uniform, thereby improving the electrochemical performance of the positive electrode material of the lithium-ion battery. At the same time, these two compounds also have good chemical stability and are not easy to decompose, which is beneficial to improve the cycle life of the material. Ammonium persulfate is a free radical initiator that can initiate free radical polymerization of polymerized monomers and promote the formation of polymers. In this preparation method, it helps to form a wet gel and catalyze the polymerization reaction, and finally generates a lithium-ion battery positive electrode material with a good structure. Ammonium persulfate is easy to use and has high efficiency.
[0041] In the present application, the amount of polymerization monomer added is 20-30% of the total mass of the product solution; the amount of cross-linking agent added is 20-30% of the total mass of the product solution; the amount of initiator added is 20-30% of the total mass of the product solution. Adding 20-30% of polymerization monomer is conducive to allowing enough monomers to participate in the polymerization reaction and form enough cross-linked structures, which can effectively prevent particle aggregation, thereby providing suitable support and dispersion effects. Adding 20-30% of cross-linking agent can effectively form a cross-linked structure and increase the stability and durability of the material. Adding 20-30% of initiator is conducive to the initiation reaction, so that the polymerization monomer forms a polymer network structure, and the polymerization reaction is more complete.
[0042] In the present application, the temperature of the above-mentioned polymerization reaction is 20-25°C, and the time of the polymerization reaction is 10-14h. Controlling the temperature and time of the polymerization reaction within the above range is conducive to better controlling the free radical polymerization of the polymerization monomer during the reaction process. This can slow down the polymerization reaction rate, help to fully carry out the polymerization process, thereby forming a uniform network structure, making the internal particle distribution of the entire wet gel more uniform.
[0043] (3) The wet gel is dried and then heat treated to obtain the anti-perovskite positive electrode material Li2M x N y SO. wherein 0<x<1, 0<y<1; M and N are different and are metal elements or metalloid elements other than lithium.
[0044] In the present application, the drying temperature is 105-120°C and the drying time is 8-10 hours. Within this temperature range, moisture can be effectively evaporated from the wet gel. This helps to reduce the water content in the material and improve the stability of the material.
[0045] In the present application, the heat treatment temperature is 300-500°C and the heat treatment time is 5-7h. Heat treatment at 300-500°C for 5-7h can fully volatilize the organic matter remaining in the wet gel, reduce the content of organic residues in the material, and thus improve the thermal stability of the material. Moreover, within the above-mentioned heat treatment temperature and time range, it is conducive to grain growth, thereby improving the crystallinity of the material, which can improve the conductivity and ion conductivity of the positive electrode material of the lithium-ion battery, and help improve the battery performance.
[0046] In the preparation method, under the initiation of an initiator, a cross-linking agent is used to cause a polymerization reaction of free radicals of a polymerizable monomer to form a three-dimensional network structure support dispersed in a wet gel, thereby preventing particle agglomeration, playing a role in refining the crystal grains, and making the crystal grains uniformly dispersed in the wet gel; and then heat-treated, the gelled organic matter is fully volatilized, thereby obtaining nano-sized Li2M x N ySO crystals. Through such a preparation method, the internal particle size of the antiperovskite positive electrode material can be made smaller and the internal particle distribution more uniform, thereby improving the cycle performance and rate performance of the lithium-ion battery.
[0047] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0048] Example 1
[0049] This embodiment provides an antiperovskite positive electrode material Li2Fe 0.5 Mn 0.5 SO, the preparation method thereof comprises the following steps:
[0050] (1) 2 mg of manganese acetate, 4 mg of ethanethiol and 6 mg of water were mixed, and a hydrolysis reaction was carried out at 25° C. The mixture was stirred at room temperature for 8 h using a magnetic stirrer to generate a hydrolysis product, methyl manganese disulfide.
[0051] The chemical equation for the hydrolysis reaction is: Mn(CH3COO)2+2C2H5SH+3H2O=Mn(SCH3)2+3CH3CH2OH+2O2
[0052] (2) adding nitric acid to adjust the pH value to 3, then adding 2 mg of ethyl iron and 4 mg of ethyl lithium to the hydrolyzate solution of step (1), adding acrylamide as a polymer monomer, ammonium persulfate as an initiator and N,N-methylenebisacrylamide as a crosslinking agent to the hydrolyzate solution to generate a wet gel, and polymerizing the free radicals of the polymer monomer to form a three-dimensional network structure support dispersed in the wet gel; wherein the amount of the polymer monomer added is 25% of the total mass of the product solution, the amount of the initiator added is 20% of the total mass of the product solution, and the amount of the crosslinking agent added is 25% of the total mass of the product solution.
[0053] The chemical equation for the polymerization reaction is: Mn(SCH3)2+(CH3CH2O)2Fe+2CH3CH2Oli+1 / 2O2+2H2O=2Li2Fe 0.5 Mn 0.5 SO+5CH3CH2OH
[0054] (3) The wet gel prepared in step (2) was dried at 115°C for 10 h, and then the dried product was heat treated at 400°C for 7 h to obtain nano-sized Li2Fe 0.5 Mn 0.5 SO crystal.
[0055] Example 2
[0056] This embodiment provides an antiperovskite positive electrode material Li2Na 0.5 Co 0.5SO, the preparation method thereof comprises the following steps:
[0057] (1) 2 mg of sodium acetate, 4 mg of ethanethiol and 2 mg of water were mixed, and a hydrolysis reaction was carried out at 25° C. The mixture was stirred at room temperature for 8 h using a magnetic stirrer to generate a hydrolysis product, sodium dimethyldithiocarbamate.
[0058] The chemical equation for the hydrolysis reaction is: 2CH3COONa+4C2H5SH+2H2O=2(CH3)2CNS2Na+6CH3OH+N2
[0059] (2) adding nitric acid to adjust the pH value to 3, then adding 1 mg of cobalt ethoxide and 4 mg of lithium ethoxide to the hydrolyzate solution of step (1), adding acrylamide as a polymer monomer, ammonium persulfate as an initiator and N,N-methylenebisacrylamide as a crosslinking agent to the hydrolyzate solution to generate a wet gel, and polymerizing the free radicals of the polymer monomer to form a three-dimensional network structure support dispersed in the wet gel; wherein the amount of the polymer monomer added is 25% of the total mass of the product solution, the amount of the initiator added is 20% of the total mass of the product solution, and the amount of the crosslinking agent added is 25% of the total mass of the product solution.
[0060] The chemical equation for the polymerization reaction is: (CH3)2CNS2Na+(CH3CH2O)3Co+4CH3CH2Oli+2O2+H2O=2Li2Na 0.5 Co 0.5 SO+7CH3CH2OH+1 / 2N2
[0061] (3) The wet gel prepared in step (2) was dried at 115° C. for 10 h, and then the dried product was heat treated at 400° C. for 7 h to obtain nano-sized Li2Na 0.5 Co 0.5 SO crystal.
[0062] The remaining embodiments and comparative examples are basically the same as embodiment 1, except that the parameters in the preparation process are different. Please see Table 1 for some parameters.
[0063] Table 1
[0064]
[0065]
[0066] Test Example 1
[0067] 1. This test example is to test the anti-perovskite cathode material Li2Fe prepared in Example 1 0.5 Mn 0.5 SO is used for material structure analysis, and its XRD diagram is as follows Figure 1 shown.
[0068] from Figure 1 It can be seen that the Li2Fe synthesized by this method 0.5 Mn 0.5 SO has good crystallinity and contains almost no impurities, indicating that this synthesis method can be used to synthesize Li2Fe 0.5 Mn 0.5 SO.
[0069] 2. This test example is for the antiperovskite cathode material Li2Fe prepared in Example 1 0.5 Mn 0.5 SO was characterized by scanning electron microscopy, and its SEM image is as follows Figure 2 shown.
[0070] from Figure 2 It can be seen that the internal particle size of the sample synthesized using this method is smaller and the internal particle distribution is more uniform.
[0071] Test Example 2
[0072] In this test example, the anti-perovskite positive electrode materials prepared in Examples 1-6, Comparative Examples 1 and 2 were mixed with a binder (PVDF, PVDF-HFP, PTFE, etc.) and a conductive agent (Super P, Ketjen black, carbon nanotubes, graphene, etc.) by a traditional scraping / spin coating method to make electrode sheets, and a commercial lithium electrolyte (1M LiPF6 in EC:DEC 1:1) and a metal lithium sheet were used as the counter electrode to prepare a half-cell, and the electrochemical charge and discharge performance was tested in a charge and discharge device.
[0073] 1. First cycle discharge capacity determination: 0.1C (1C = 230mA g -1 ) is the discharge capacity in grams when discharged to the lower voltage limit.
[0074] 2. Coulomb efficiency: (first discharge capacity / first charge capacity)*100%.
[0075] 3. Place the battery in a 25°C constant temperature box at 0.1C (1C = 230mAg -1 ) current, constant current charge and discharge test, the charge and discharge voltage range is 1.2-3V, observe the battery capacity attenuation and battery efficiency changes.
[0076] 4. Rate performance: The test method is to first activate at a rate of 0.05C, and then perform charge and discharge tests at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 0.1C respectively.
[0077] 4. Cycle performance: The test method is to first activate at a rate of 0.05C, and then perform charge and discharge tests at 0.1C.
[0078] The test results of the above items are shown in Table 2, where the charge and discharge curves of the battery prepared by the positive electrode material provided in Example 1 are shown in Table 2. Figure 3 As shown, the rate performance diagram of the battery prepared by the positive electrode material provided in Example 1 is as follows Figure 4 shown.
[0079] Table 2
[0080]
[0081] From Table 2, Figure 3 and Figure 4 It can be seen that the battery prepared with the positive electrode material provided in Example 1 has a first cycle charge capacity of 366 mAh / g, a first cycle discharge capacity of 362 mAh / g, and a first coulombic efficiency of 99%. Moreover, it can still maintain 0.28 Ahg at 1C. -1 The capacity is about 0.046Ah g at a rate of 5C. -1 The specific capacity is because the material prepared by the preparation method provided by the present application has a small particle size and a uniform powder distribution, which is conducive to ion transmission.
[0082] By comparing Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that when the pH is 2-4, the electrochemical performance of the battery is good, under which the hydrolysis reaction and polymerization reaction rates are balanced, the yield is high, and the grains are uniform. When the pH is lower than 2, the hydrolysis reaction rate is fast and the polymerization reaction rate is slow, resulting in incomplete polymerization; and when the pH value is higher than 4, the hydrolysis rate is low and the polymerization reaction rate is fast, resulting in incomplete hydrolysis; therefore, the electrochemical performance of the battery finally prepared is poor.
[0083] By comparing Examples 1, 3 and 4, it can be found that when the amount of cross-linking agent added is 20-30% of the total mass of the product solution, the electrochemical performance of the battery is better. When the amount of cross-linking agent is small (less than 20%), the degree of grain refinement will decrease, because less cross-linking agent cannot form a dense three-dimensional network and cannot prevent particle agglomeration; when the amount of cross-linking agent is large (greater than 30%), the cross-linking agent forms a network structure in the solution, and these network structures will cross each other to form more gaps and voids, making the gel structure looser, resulting in a decrease in the stability of the gel.
[0084] By comparing Examples 1, 5 and 6, it can be found that when the heat treatment temperature is 300-500°C, the electrochemical performance of the battery is better. When the heat treatment temperature is lower than 300°C, it will affect the decomposition of organic matter, resulting in incomplete decomposition of organic matter; when the heat treatment temperature is higher than 500°C, it will cause grain growth, and excessively large grains may cause the conductivity of the material to decrease, affecting the battery performance.
[0085] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A method for preparing an antiperovskite positive electrode material, characterized in that: include: Mixing a metal salt containing metal M with ethanethiol and water to perform a hydrolysis reaction to obtain a product solution; The pH of the product solution is adjusted to 2-4, and a metal salt containing metal N, lithium ethoxide, a polymerization monomer, a crosslinking agent and an initiator are added to the product solution to carry out a polymerization reaction to generate a wet gel; The wet gel is dried and then heat treated to obtain the antiperovskite positive electrode material Li2M x N y SO; Among them, 0<x<1, 0<y<1; The M and N are different and are metal elements or metalloid elements other than lithium; the metal salt includes carboxylate and / or alkoxide; The polymerizable monomer includes a vinyl monomer or an acrylic monomer.
2. The preparation method according to claim 1, characterized in that: M and N each independently include any one of Na, K, Mg, Ca, Sr, Ba, Zn, Sc, Y, Al, Ga, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Si, Sn and Sb; Optionally, the metal salt includes at least one of manganese acetate, sodium acetate, iron ethoxide and cobalt ethoxide.
3. The preparation method according to claim 1, characterized in that: The acrylic monomer includes acrylamide; Optionally, the vinyl monomer includes any one of ethylene, propylene and acrylic acid; Optionally, the crosslinking agent includes any one of N,N-methylenebisacrylamide and divinyldisiloxane; Optionally, the initiator comprises ammonium persulfate.
4. The preparation method according to any one of claims 1 to 3, characterized in that The temperature of the hydrolysis reaction is 20-25°C, and the time of the hydrolysis reaction is 6-8h; Optionally, the polymerization reaction temperature is 20-25° C., and the polymerization reaction time is 10-14 h.
5. The preparation method according to any one of claims 1 to 3, characterized in that: The drying temperature is 105-120°C, and the drying time is 8-10h; Optionally, the temperature of the heat treatment is 300-500° C., and the time of the heat treatment is 5-7 hours.
6. The preparation method according to any one of claims 1 to 3, characterized in that: The amount of the polymerization monomer added is 20-30% of the total mass of the product solution; Optionally, the amount of the cross-linking agent added is 20-30% of the total mass of the product solution.
7. The preparation method according to any one of claims 1 to 3, characterized in that: The added amount of the initiator is 20-30% of the total mass of the product solution.
8. The preparation method according to any one of claims 1 to 3, characterized in that: The particle size of the antiperovskite positive electrode material is 50-100 nm.
9. An antiperovskite positive electrode material, characterized in that: An anti-perovskite positive electrode material prepared by the preparation method described in any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: Comprising the antiperovskite positive electrode material as described in claim 9.
Citation Information
Patent Citations
Battery separator, preparation method of battery separator and lithium ion battery
CN109428038A
Lithium ion battery composite positive electrode material, preparation method thereof and lithium ion battery
CN113380990A
Electrolyte, preparation method thereof and lithium ion battery containing electrolyte
CN115411361A
Artificial SEI material, metal lithium negative electrode and preparation method and application thereof
CN116613316A
Preparation method of Eu < 2 + >-based perovskite-hydrogel compound and flexible X-ray detector
CN118406184A